Intra-operative recordings of local field potentials can help localize the subthalamic nucleus in Parkinson's disease surgery. - Chen, C; Pogosyan, A; Zrinzo, L; Tisch, S; Limousin, P; Ashkan, K; Yousry, T; Hariz, M; Brown, P (2006)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) can be a highly effective treatment for Parkinson's disease (PD). However, therapeutic efficacy is limited by difficulties in consistently and correctly targeting this nucleus. Increasing evidence suggests that there is abnormal synchronization of beta frequency band activity (approximately 20 Hz) in the STN of PD patients, as reflected in the oscillatory nature of the local field potential (LFP). We hypothesized that an increase in the power of the LFP beta activity may provide intra-operative confirmation of STN targeting in patients undergoing STN implantation for the treatment of advanced PD. Accordingly, we recorded LFPs from the four contacts of DBS electrodes as the latter were advanced in 2 mm steps from a point 4-6 mm above the intended surgical target point in the STN, to a point 4 mm below this. Contacts were configured to give three bipolar recordings of LFPs. These were analyzed on 16 sides in 9 patients. The power in the 13-35 Hz band recorded at the lowest contact pair underwent a steep but focal increase during electrode descent. The depth of the peak beta activity showed excellent agreement with the level of the intra-operative clinical stun effect (k coefficient = 0.792). The depth of peak beta activity also showed 100% specificity and 100% sensitivity for placement within STN in comparison to pre- and Post-operative stereotactic MRI. Functional physiological localization of STN by the on-line spectral analysis of LFPs is quick to perform and may provide information directly relevant to the position of the electrode contact actually used for DBS.